Potential of Biosurfactant Extracted from Averrhoa bilimbi Leaves Using the Maceration Method - Cindy Dwi Sekar Arum; Cintiya Septa Hasannah; Alfieta Rohmaful Aeni (Research in Chemical Engineering, 2025)
The utilization of natural resources as raw materials for biosurfactants is increasingly urgent to reduce dependence on synthetic surfactants that have the potential to pollute the environment. One potential natural source is Averrhoa bilimbi leaves, which contain chemical compounds such as saponins. This compound acts as a natural biosurfactant that is not only effective but also environmentally friendly, so it can be a solution in overcoming the negative impact of synthetic surfactant use. This study aims to determine the optimal level of saponin as a biosurfactant from starfruit wuluh (Averrhoa bilimbi) by varying the ratio of starfruit leaf extraction and solvent, as well as examining the height and stability of foam produced by saponin from starfruit wuluh leaves. In addition, this study evaluated the effect of pH on the performance of saponin from star fruit as a biosurfactant. The method used was maceration extraction using ethanol solvent. Saponin testing was carried out by Thin Layer Chromatography (TLC) test to determine the saponin content of each sample. The test results showed that the highest saponin content was found in the starfruit leaf extraction: solvent ratio variation of 1:12, namely 6.12%, while the best foam height and foam stability test results were found in the starfruit leaf extraction: solvent ratio variation of 1:10, where no foam disappeared for 15 minutes. The pH test showed that pH 7 is considered safe for the environment. Thus, saponin extract from belimbing wuluh leaves has the potential to be an effective and sustainable biosurfactant, which can be a more environmentally friendly alternative to synthetic chemical-based surfactants.